IP telephony using CallManager express lab portfolio - Schmidt, Cheryl A., 1961- (Cisco Press, 2007)
IP Telephony Using CallManager Express Lab Portfolio provides a hands-on approach to learning the basic principles of voice over IP (VoIP) to build a voice-enabled network for the small to medium-sized business. As you work through the 51 labs in the book, you learn how to deploy a basic phone system using a CallManager Express-capable router. You install, configure, and customize Cisco® IP Phones to work in an IP Telephony environment as well as with traditional analog telephony devices. Each chapter begins with an explanation of the converging technology used within that chapter's labs and, where necessary, includes a refresher on routing and switching topics so that you can properly set up the labs. The collection of labs features clear objectives, equipment needs, alternative methods, and probing questions. Additionally, the book includes a command reference as one of the six supplemental appendixes. All the material has been written and tested with students in a live classroom environment: Labs enable you to deploy a progressively more layered VoIP environment as you complete the labs in each chapter. Paper exercises help you work through and reinforce your understanding of fundamental topics such as dial plans, IP addressing, and dial peers. Case Study labs present the material in scenarios that combine the methods learned in the previous chapters so that you apply your knowledge to a specific scenario or task. Pulling together various concepts simulates the real-world environment where things are rarely assigned one step at a time. The Lab Portfolio can be used as a supplement to any textbook used to teach CVoice or CallManager Express. It can also be used as a standalone resource for anyone wanting to learn the basics of IP Telephony. After completing all the exercises and hands-on labs in this book, you will know how VoIP works and be well prepared to configure the technology in a small to medium-sized business. Use this Lab Portfolio with: Cisco IP Communications Express: CallManager Express with Cisco Unity Express ISBN: 1-58705-180-X Voice over IP Fundamentals, Second Edition ISBN: 1-58705-257-1 This book is part of the Networking Technology Series from Cisco Press®, the only authorized publisher for Cisco Systems®.